Catastrophic health expenditure and health-related quality of life among older adults in Shandong, China: the moderation effect of daily care by adult children - Jiayan Li; Tingting Gao; Dan Zhao; Shujun Chai; Jingjing Luo; Xuehong Wang; Xueqing Wang; Jingjie Sun; Peilong Li; Chengchao Zhou (BMC, 2024)
Abstract Background Catastrophic health expenditure (CHE) has a considerable impact on older people in later life, but little is known about the relationship between catastrophic health expenditure and health-related quality of life (HRQOL). The aim of this study was to examine the relationship between catastrophic health expenditure and health-related quality of life in older people, and to explore whether the daily care provided by adult children is a moderator in this relationship. Methods Data from the sixth National Health Services Survey in Shandong Province, China. The sample consisted of 8599 elderly people (age ≥ 60 years; 51.7% of female). Health-related quality of life was measured by the health utility value of EQ-5D-3 L. Interaction effects were analyzed using Tobit regression models and marginal effects analysis. Results The catastrophic health expenditure prevalence was 60.5% among older people in Shandong, China. catastrophic health expenditure was significantly associated with lower health-related quality of life (β= − 0.142, P < 0.001). We found that adult children providing daily care services to their parents mitigated the effect of catastrophic health expenditure on health-related quality of life among older people (β = 0.027, P = 0.040). Conclusions Our findings suggested that catastrophic health expenditure was associated with health-related quality of life and the caring role of older adult children moderated this relationship. Reducing the damage caused by catastrophic health expenditure helps to improve health-related quality of life in older people. Adult children should increase intergenerational contact, provide timely financial and emotional support to reduce the negative impact of catastrophic health expenditure on health-related quality of life.